208k views
0 votes
An equation is shown below: 4(x − 3) − 5(x + 1) = 3 Which statement shows a correct next step in solving the equation? (1 point) The equation can become 4x − 12 − 5x − 5 = 3 by applying the associative property of multiplication. The equation can become 4x − 3 − 5x + 1 = 3 by applying the associative property of multiplication. The equation can become 4x − 3 − 5x + 1 = 3 by applying the distributive property. The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

User Juan Vega
by
4.9k points

1 Answer

1 vote

Answer:

The equation can become 4x − 12 − 5x − 5 = 3 by applying the distributive property.

User Ssayan
by
5.2k points